KELAYAKAN MODUL SUBMATERI STRUKTUR DAN FUNGSI JARINGAN TUMBUHAN XI SMA BERDASARKAN JUMLAH DAN UKURAN STOMATA MONOKOTIL - yarso, Sunarseh; Daningsih, Entin; Marlina, Reni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to determine the feasibility of module on submatrial structure and function of plant tissue in class XI high school with addition of the results from study  of number and size stomata of monocot plants. The research was descriptive with purposive sampling technique using two stages of validation namely instrument and module validation. Instrument was validated by three validators, namely two lecturers of biology education and one biology teacher while the module was validated by five validators namely two biology education lecturers and three biology teachers who implemented the 2013 curriculum. The instrument sheet contained six aspects and eleven criteria. Data were analyzed by CVR and CVI formulas using Lawshe method. The results of instrument validation showed  that the instrument sheet was suitable to use and  corrected while the module obtained CVR and CVI values of 0.99 in accordance with the minimum value of the Lawshe so that it was declared valid and feasible to be used as a teaching materials on submatrial structure and function of plant tissue in class XI high school.Keywords: module, number and size of stomata, monocot